INCIDENCE OF PNEUMOTHORAX IN CASES WITH ARDS REQUIRING PEEP > 10 mmHg - AHMAD, M; IQBAL, A; BASHIR, I; NAEEM, OM; ARSHAD, U; KIRAN, M (Biological and Clinical Sciences Research Journal, 2023)
This study aimed to determine the incidence of pneumothorax in patients with ARDS who require PEEP levels higher than ten mmHg. The study was conducted at the Department of Pulmonology and Critical Care, Central Park Teaching Hospital in Lahore, from January 2022 to June 2023. One hundred thirty-eight patients were enrolled in this cross-sectional study, and informed consent was obtained from all patients and their guardians. All patients underwent chest radiography or point of care ultrasound (POCUS) to identify pneumothorax. The results showed that 35 out of 138 patients (25.4%) had pneumothorax, and the mean PEEP value was 11.05±1.05. The study also found that male patients were more commonly affected than female patients (56.5% vs 42.8%). The practical implication of this study is that the diagnosis of pneumothorax is crucial in patients with ARDS, especially in the early stages, as this condition can lead to high mortality rates. The study can help pulmonologists choose better patient treatment options and avoid comorbidities. Conservative management may be recommended to patients if there are no clinical signs or symptoms of a severe condition and if the pneumothorax size is small. In conclusion, this study shows that patients with ARDS requiring PEEP levels higher than ten mmHg are at a higher risk of developing pneumothorax. Thus, early diagnosis and proper management are essential to improve patient outcomes.